(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Diabetic nephropathy is a common microvascular complication of diabetes mellitus and is a cause of significant morbidity and mortality. This study explores the relationship of HbA1c with diabetic nephropathy in Pakistani population. Patients and methods: A cross-sectional study was conducted at the Internal Medicine Department of Shaikh Zayed Medical Complex (SZMC), Lahore, on patients with type 2 diabetes. Mean HbA1C levels were compared between patients with and without diabetic nephropathy by applying independent sample t-test, while suboptimal glycemic control was compared using chi-square test. Pearson’s correlation was applied to assess the correlation of urinary albumin levels with duration of diabetes and HbA1c levels. Results: A total of 80 patients with type 2 diabetes mellitus were included in the study. The mean age of all the participants was 47 + 10 years. Out of these cases, 56.3% were male and 43.8% were female. Suboptimal glycemic control was present in 72.5% cases and 47.5% were diagnosed with diabetic nephropathy. Higher mean HbA1c levels were observed in the patients with nephropathy as compared to those without nephropathy (10.1 + 1.1% vs 7.2 + 0.8%, p < 0.001). All diabetic nephropathy cases (100%) had suboptimal glycemic control as compared to 47.6% of the cases without nephropathy (p < 0.001). The 24-hours urinary proteins had a strong correlation with HbA1c levels (r = 0.771, p < 0.001) and a moderate correlation with duration of diabetes (r = 0.638, p <0.001). In multivariate regression analysis, only obesity significantly predicted suboptimal glycemic control (OR: 4.346, 95% CI: 1.162 – 16.249, p = 0.029). Conclusion: There is a significant association between diabetic nephropathy and suboptimal glycemic control. The urinary albumin levels have positive correlation with HbA1c levels and duration of diabetes. Obesity is a significant predictor of suboptimal glycemic control in Pakistani population. There is need to explore the factors contributing towards diabetic nephropathy in patients with diabetes.